The Origins of Tree Names in Celtic - Quentel, Gilles (Studia Celtica Posnaniensia, 2018)
This paper deals with the long-debated question of the origins of tree names and the methodological problems related to PIE etymologies. It aims at putting forward some basic principles of etymology, and at applying these principles to the analysis of twelve tree names. It also seeks to demonstrate the relevance of substratic pre-IE languages’ influence on the lexicon, and at isolating geographic areas corresponding to pre-Indo-European lexical stocks lying behind modern Celtic languages.